2012
DOI: 10.1111/iji.12032
|View full text |Cite
|
Sign up to set email alerts
|

16th IHIW: Anti‐HLA alloantibodies of the of IgA isotype in re‐transplant candidates

Abstract: In this multicentre study, sera from 803 retransplant candidates, including 775 kidney transplant recipients, were analysed with regard to the presence and specificity of anti-HLA alloantibodies of the IgA isotype using a modified microsphere-based platform. Of the kidney recipients, nearly one-third (n = 237, 31%) had IgA alloantibodies. Mostly, these antibodies were found in sera that also harboured IgG alloantibodies that could be found in a total of 572 (74%) of patients. Interestingly, IgA anti-HLA antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 10 publications
1
17
1
2
Order By: Relevance
“…The Luminex assay has the great advantage of allowing the use of a variety of secondary detection antibodies to assess immunoglobulin isotypes [22] or subclasses [23] as well as complement components [24]. …”
Section: Principles Of the Luminex Methodsmentioning
confidence: 99%
“…The Luminex assay has the great advantage of allowing the use of a variety of secondary detection antibodies to assess immunoglobulin isotypes [22] or subclasses [23] as well as complement components [24]. …”
Section: Principles Of the Luminex Methodsmentioning
confidence: 99%
“…Recently, however, the impact of other complement‐fixing and also noncomplement‐fixing antibody isotypes on graft survival has gained attention (Chen, Sequeira, & Tyan, ). As part of the 16th International HLA and Immunogenetics Workshop, we reported a high prevalence of anti‐HLA IgA in a large cohort of re‐transplantation candidates (Arnold et al., ). Expanding these findings, we now assessed the impact of the presence and specificity of anti‐HLA IgA alloantibodies on graft survival in a subset of 694 kidney re‐transplantation patients.…”
Section: Introductionmentioning
confidence: 97%
“… Summary We reported previously on the widespread occurrence of anti‐ HLA alloantibodies of the IgA isotype (anti‐ HLA IgA) in the sera of solid‐organ re‐transplantation (re‐tx) candidates (Arnold et al., ). Specifically focussing on kidney re‐tx patients, we now extended our earlier findings by examining the impact of the presence and donor specificity of anti‐ HLA IgA on graft survival.…”
mentioning
confidence: 99%
“…Clinical studies have shown that both pre-existence and de novo production of IgG donor-specific antibodies (DSA) are strongly associated with acute and chronic allograft injury in kidney, heart, lung, and to some extent, liver transplantation (2934). On the contrary, studies on IgM and IgA DSA did not reveal any isolated effect of these isotypes on allograft outcome unless they were co-existent with IgG antibodies (35, 36). This indicates that the above described GC response needs to be active for pathological antibody response to occur in the setting of organ transplantation.…”
Section: Significance Of Antibody Responses In Solid Organ Transplantmentioning
confidence: 82%